Justifying Atrocities: The Effect of Moral-Disengagement Strategies on Socially Shared Retrieval-Induced Forgetting. (June 2014) - Coman, Alin; Stone, Charles B.; Castano, Emanuele; Hirst, William
A burgeoning literature has established that exposure to atrocities committed by in-group members triggers moral-disengagement strategies. There is little research, however, on how such moral disengagement affects the degree to which conversations shape people's memories of the atrocities and subsequent justifications for those atrocities. We built on the finding that a speaker's selective recounting of past events can result in retrieval-induced forgetting of related, unretrieved memories for both the speaker and the listener. In the present study, we investigated whether American participants listening to the selective remembering of atrocities committed by American soldiers (in-group condition) or Afghan soldiers (out-group condition) resulted in the retrieval-induced forgetting of unmentioned justifications. Consistent with a motivated-recall account, results showed that the way people's memories are shaped by selective discussions of atrocities depends on group-membership status.